Virulence and Antimicrobial Resistance Profiling of Aeromonas hydrophila Recovered from Retail fish in Sharkia Province, Egypt - Morshdy, Alaa Eldin M.A.; Ahmed, Ghada Eid; El-tahlawy, Ahmed S.; El Bayomi, Rasha M.; Mahmoud, Abdallah Fikry A. (Journal of Advanced Veterinary Research, 2023)
Fish is one of the most important foods because of its high nutritional value, high palatability, and easy digestion. At the same time, it acts as a vehicle for many types of pathogenic microorganisms especially Aeromonas species, which results in public health hazards. Therefore, the present study was conducted to evaluate the prevalence of Aeromonas species in fresh fish (catfish, mullet, lizardfish, and coralfish) marketed in Zagazig city, Sharkia Governorate, Egypt. In addition, multiplex PCR was performed to detect some virulence-associated genes in A. hydrophila isolates. Furthermore, antimicrobial susceptibility testing was carried out on A. hydrophila isolates using commonly used antimicrobials in Egypt through the disc diffusion method. The achieved results indicated contamination of fish with different species of Aeromonas such as A. veronii, A. sobria, A. caviae and A. hydrophila. The results revealed that Aeromonas species isolated with an overall percentage of 55% of all examined fish. Bacteriological examinations revealed 20% A. hydrophila, 20% A. sobria, 10% A. caviae and 5% A. veronii. Antibiotic sensitivity declared high resistance of the isolates to different antimicrobial agents used in Egypt, including penicillin (100%), Ampicillin (90.0%), Streptomycin (90.9%), Cephalothin (72.7%), Tetracycline (72.7%), Cefotaxime (63.6%), and Sulfamethoxazole (54.5%). Therefore, hygienic measures should be adopted to control microbial contamination either in the aquatic environment or in fish markets.